Engineering Protein Self‐Assembly: A New Approach for the Design of Octahedral Cages. (28th October 2016) - Cougnon, Fabien B. L.
Abstract : A new symmetry‐based approach allowed the self‐assembly of an octahedral protein nanostructure. C 3 trimeric and C 4 tetrameric oligomerization domains can be combined in an engineered protein to direct assembly into a desired object. This work might provide the basis for a more general and flexible strategy to control protein self‐assembly.